Morphing Winglet Design for Aerodynamic Performance Optimization of the CRJ-700 Aircraft. Part 1 – Structural Design - Paul MEYRAN (National Institute for Aerospace Research “Elie Carafoli” - INCAS, 2021)
This study aims to design a morphing winglet structure for the CRJ-700 regional transport aircraft. The morphing technology is applied on winglets to demonstrate a significant increase of the aerodynamic performance of aircraft. From the aerodynamic data of the LARCASE Virtual Research Simulator VRESIM, the aerodynamic benefits in the cruising phase were obtained through a study on the ParaView software. The morphing winglet design was drawn using CATIA V5; this new concept included several structural components, as well as a simple and light mechanism allowing to orientate the winglet angles between 90° and -90° of inclination. The structural model was exported to HyperMesh structural analysis software. Maximum stresses were obtained, and the model demonstrated its resistance to maximum aerodynamic loads as well as load factors of -2G to 7G.